Analysis of Emotional Intelligence on Communication Skills Mediated by Nurses' Job Satisfaction at Pidie Jaya Regional General Hospital - Zuhra Afianda; Chrimis Novalinda Ginting; Adek Armansyah (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
This study investigates the intricate relationship between emotional intelligence (EI), communication skills, and job satisfaction among nurses at Pidie Jaya Regional General Hospital. Focusing on the mediating role of job satisfaction, this qualitative analysis synthesizes findings from recent research to elucidate how these factors interact to influence nursing performance and the quality of patient care. Data, gathered from in-depth interviews with 15 nurses, were analyzed using thematic analysis. Key themes revealed that EI significantly enhances communication skills, with emotional awareness, empathy, and emotional regulation playing crucial roles. Job satisfaction, influenced by organizational support, professional development opportunities, and work-life balance, acts as a critical mediator, fostering positive attitudes and effective communication practices. The combined effect of high EI, strong communication skills, and job satisfaction leads to improved patient satisfaction, enhanced teamwork, and reduced errors, impacting overall healthcare outcomes. The study underscores the importance of EI training and supportive work environments in improving nurse performance and quality of care, advocating for holistic approaches that integrate these factors to optimize healthcare delivery.